The Effect of Promotion and Addiction Attitudes in the Use of Tiktok on Impulse Buying Behavior Review of Maslahah (Empirical Study of the Hamlet Community Butuh Sidowarno Wonosari) - Mohammad Syifa urrosyidin; Rihan Nurulaini (Al-Muamalat: Journal of Islamic Economics Law, 2025)
ENGLISH The Tiktok application is the application with the most users in the world as well as in Indonesia, which is 106.52 million users in October 2023 and continues to increase. The promotion of the sale of goods and sales techniques that cause most of its users (especially in the Butuh Sidowarno Wonosari Hamlet Community) in the end cannot be separated from the application or in other words addicted to its use. This study mixes methods with The Explanatory Sequential Design method. SPSS 25 application, Sample taken 10% of the population of 100 people. The technique used was quantitative data analysis in the context of empirical studies with multiple linear regression analysis. With the results of 1) Addiction Attitude (X1) has a significant effect on Impulse Buying Behavior. 2) Promotion has a positive influence on impulse buying behavior on the Tiktok application. 3) Addiction and Promotion Attitude Variables can affect Impulse Buying Behavior together. And if we look at the law of maslahah, then, the second part of promotion and attitude of addiction does not include maslahah because it leads to more mudharat. Based on the results of this study, it can be proven that the attitude of addiction or promotion has a significant effect on impulse buying behavior in people in Butuh Hamlet. 2) Promotion and Addiction Attitude that affects Impulse Buying behavior is not part of Maslahah because it is not in accordance with the provisions contained in Islam INDONESIA Aplikasi Tiktok adalah aplikasi dengan pengguna terbanyak di dunia juga di Indonesia yaitu 106,52 juta pengguna pada Oktober 2023 dan terus meningkat. Promosi penjualan barang dan teknik penjualan yang menyebabkan kebanyakan penggunanya (terkhusus pada Masyarakat Dusun Butuh Sidowarno Wonosari) pada akhirnya tak bisa terlepas dari aplikasi tersebut atau dengan kata lain kecanduan dalam penggunannya. Penelitian ini Mix Methods dengan metode The Explanatory Sequential Design. Aplikasi SPSS 25, Sampel yang diambil 10% dari populasi 100 orang. Teknik yang digunakan analisis data kuantitatif dalam konteks studi empiris dengan analisis regresi linear berganda. Dengan hasil 1) Sikap Adiksi (X1) berpengaruh signifikan terhadap Perilaku Impulse Buying. 2) promosi memiliki pengaruh positif terhadap perilaku impulsive buying pada aplikasi Tiktok. 3) Variabel Sikap Adiksi dan Promosi dapat mempengaruhi Perilaku Impulse Buying secara bersama-sama. Dan apabila ditinjau dari hukum maslahah maka, kedua dari promosi dan sikap adiksi tidak termasuk kepada Maslahah karena lebih banyak membawa kepada hal mudharat.Berdasarkan hasil penelitian ini dapat dibuktikan bahwasanya Sikap adiksi ataupun Promosi berpengaruh secara signifikan terhadap perilaku Impulse buying pada masyarakat yang berada di Dusun Butuh. 2) Promosi dan Sikap Adiksi yang mempengaruhi perilaku Impulse Buying ini bukanlah bagian dari Maslahah dikarenakan tidak sesuai dengan ketentuan yang terdapat dalam Islam.